PENEMUAN HUKUM UNTUK PENEGAKAN UNDANG-UNDANG PORNOGRAFI - Arikha Saputra (Jurnal Ilmiah Dinamika Hukum, 2017)
The polemics of pornography legislation passed by the legislature are still centered on the lack of clarity in the definition of "porno" or "pornography". This has led to various conflicts or contradictions between various circles, especially the culture or culture of certain regions, which have an impact on the great potential for disintegration among regions in Indonesia, only because of the unclear and uncertainty of the establishment of the Pornography Act and its application which is inconsistent with Community culture. This evokes the author discusses the discovery of law for the enforcement of the Pornography Act against the diversity of the culture of Indonesian society. The purpose of research is to suppress and reduce the impact and distribution of pornographic material then one of the solutions is through the norms that exist in the community formed by the habits of society, so that at least can be obeyed and carried out in accordance with the norms in the community Because, these norms are a reflection of the habits of behavior (culture) of society in everyday life. Thus the definition of pornography, perception of pornography and application of pornography is different for every region in Indonesia, let alone a diverse culture. The pornography law that has been enacted should be able to ward off a crime or action to make the culprit a culprit, and of course also must meet the sense of community justice. The community's sense of justice here against the Pornography Act is how to balance the customary norms contained within the society which are to provide the moral guidance and moral education of the community.